2014
DOI: 10.1007/s00405-013-2756-x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms in chronic rhinosinusitis with polyps: is eradication possible?

Abstract: The objective of the study was to reveal if mometasone furoate nasal spray as monotherapy or combined with long-term oral clarithromycin have influence on biofilms in chronic rhinosinusitis with polyps. The study is a randomized controlled trial in a tertiary referral hospital. Thirty-four patients with chronic rhinosinusitis completed the study. In the first group, 19 patients received mometasone furoate nasal spray 200 μg once daily for 8 weeks. In the second group, 15 patients received oral clarithromycin 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 13 publications
1
41
1
Order By: Relevance
“…After assessing 94 full‐text articles for eligibility, an additional 77 studies were excluded. Finally, 17 RCTs with 1738 participants were included in this systematic review (Fig. ), and 16 RCTs with available data were included in the meta‐analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After assessing 94 full‐text articles for eligibility, an additional 77 studies were excluded. Finally, 17 RCTs with 1738 participants were included in this systematic review (Fig. ), and 16 RCTs with available data were included in the meta‐analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of each included study ranged from 43 to 345. Fifteen studies were conducted in China, 1 study was conducted in Turkey, and 1 study was conducted in Russia . All studies reported using systemic treatment with oral clarithromycin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While overall biofilm prevalence decreased with treatment in both groups (75% vs 43.8%), and post-treatment grade was significantly decreased in both groups (median difference = 1.0, p <0.01), no additional benefit was found for adding intranasal steroid to oral macrolide therapy in CRSwNP [11]. In a similar RCT, Korkmaz et al compared the efficacy of intranasal steroid as monotherapy versus combined with low-dose oral macrolide in 34 CRSwNP patients [70]. The combined macrolide and intranasal steroid group had significant reduction of biofilm compared to control but the intranasal steroid group alone did not.…”
Section: Emerging Treatmentsmentioning
confidence: 99%